RELIGION AND POLITICS: INTERPRETATIONS OF GANDHI, NEHRU AND AMBEDKAR - Kadankavil, Thomas (Journal of Dharma, 2000)
Today we witness a number of inter-religious conflicts, international disputes, socio-economic inequalities, social prejudices, north-south division of nations for world market and superpower and excessive exploitation of nature. The ideal of peaceful co-existence of nations under the political principle of panchasila is threatened by ever increasing fanatical terrorist groups organized on the basis of colour, race, ethnicity, class, caste, religion and nation. The growing cult of violence along with the degeneration of moral values does not auger well for the whole of mankind. Racial discrimination, suppression of freedom of opinion, religious intolerance, criminalization of politics, tacit sanction given to consumerism and corruption are the present day social evils with which we can have no compromise. In the history of the Indian struggle for independence several great statesmen who reflected seriously on these have offered their own vision for a better society where religion and politics play their own proper role. We select Gandhi,Nehru and Ambedkar, representatives of different or even opposing line of thinking for our special study.